Cross-country Consumption Risk Sharing, a Long-run Perspective - Qiao, Zhaogang (IMF Working Papers; Working Paper ;, 2010)
This paper estimates an empirical nonstationary panel regression model that tests long-run consumption risk sharing across a sample of OECD and emerging market (EM) countries. This is in contrast to the existing literature on consumption risk sharing, which is mainly about risks at business cycle frequency. Since our methodology focuses on identifying cointegrating relationships while allowing for arbitrary short-run dynamics, we can obtain a consistent estimate of long-run risk sharing while disregarding any short-run nuisance factors. Our results show that long-run risk sharing in OECD countries increased more than that in EM countries during the past two decades.